English Language Needs Assessment for Economics Students: An ESP Analysis - Yessicka Noviasmy; Nurul Hasanah Hasanah (Universitas Muhammadiyah Barru, 2025)
This research aims to identify and analyze the English language learning needs of non-English major students, specifically those studying economics. Utilizing a questionnaire distributed among students, the findings reveal that a significant majority (80%) perceive their English proficiency as beginner level, highlighting an urgent need for foundational language skills relevant to their field of study. The results indicate a strong preference for practical learning materials, particularly those related to economics, such as reading economic materials (70.6%), speaking skills with clients (76.5%), and mastering vocabulary related to economics (65.7%). Furthermore, the analysis highlights a gap between the current knowledge and the proficiency required for academic and professional contexts. Students expressed a desire to engage in learning activities that promote interaction and collaboration, emphasizing the importance of developing a curriculum tailored to their specific needs. This study underscores the necessity of implementing a needs-based curriculum that incorporates active learning strategies, thereby enhancing students' English language skills and preparing them for future workplace challenges in the field of economics.